CSOs seen through the optic of the European Commission: has the Commission's perspective changed following the refugee crisis and the populist turn?. Issue 4 (8th August 2021) - Pejovic, Milica; Cossarini, Paolo
ABSTRACT: This article examines the European Commission's discourse to identify whether and how the Commission's perception of the role of civil society organisations (CSOs) has evolved in the context of the refugee crisis and the rise of right-wing populism. To this end, we conduct thematic and frame analyses of a variegated data set consisting of announcements, speeches, press releases, and statements published by the Commission between 2013 and 2018. The article shows that the 'refugee crisis' and the populist turn have changed the European Commission's view of CSOs, particularly concerning their democratic function within the European Union set-up as providers of input legitimacy. The lower profile given to civil society in the Commission's discourse following the surge in populism and growing animosities towards non-governmental organisations signals a discursive turn in the Commission's perception of CSOs as catalysers of participative and deliberative democracy as well as of policy-making informed by CSO expertise. However, the Commission has framed CSOs as important contributors to the output legitimacy of European Union policies, emphasising the role of civil society in the implementation of migration policies through socioeconomic reforms, providing services, and 'debunking' migration-related information.